Influence of the composition gradient on the propagation of heat pulses in functionally graded nanomaterials. (31st January 2019) - Cao, B.-Y.; Di Domenico, M.; Nie, B.-D.; Sellitto, A.
Abstract : A theoretical model to describe heat transport in functionally graded nanomaterials is developed in the framework of extended thermodynamics. The heat-transport equation used in our theoretical model is of the Maxwell–Cattaneo type. We study the propagation of acceleration waves in functionally graded materials (FGMs). In the special case of functionally graded Si1− c Ge c thin layers, we point out the influence of the composition gradient on the propagation of heat pulses. A possible use of heat pulses as exploring tool to infer the inner composition of FGMs is suggested.